Determining Labour and Skills Shortages and the Need for Labour Migration in Ireland - Gusciute, Egle; Quinn, Emma; Barrett, Alan (ESRI, 2015)
This study explores the extent to which research on the Irish labour market guides economic migration policy-making. An overview is provided of the process in place for identifying labour and skills shortages, and the mechanisms and tools used for that purpose. The study shows that direct information linkages exist between the responsible bodies: the Skills and labour Market Research Unit (SLMRU) in SOLAS and the Department of Jobs, Enterprise and Innovation (DJEI), and that cooperation has become more formalised in recent years. The relationship between identified skills needs and permits issued is evident. Of all employment permits issued in 2014 almost 70 per cent were issued to professionals: 43 per cent were issued in the IT sector and 25 per cent were issued in the healthcare sector. This report is based on the Irish contribution to an EU-wide European Migration Network (EMN) study, which shows that Ireland is ahead among the 25 participating EU member states, in terms of linking labour market information to economic permits. (See: European Migration Network, 2015. Determining labour shortages and the need for labour migration from third countries in the EU).